EFNS review on the role of muscle biopsy in the investigation of myalgia. Issue 7 (30th April 2013) - Kyriakides, T.; Angelini, C.; Schaefer, J.; Mongini, T.; Siciliano, G.; Sacconi, S.; Joseph, J.; Burgunder, J. M.; Bindoff, L. A.; Vissing, J.; de, M.; Hilton‐Jones, D.
<x xml:space="preserve">Abstract</x> Background Myalgia, defined as any pain perceived in muscle, is very common in the general population and a frequent cause for referral to neurologists, rheumatologists and internists in general. It is however only rarely due to primary muscle disease and often referred from ligaments, joints, bones, the peripheral and central nervous system. A muscle biopsy should only be performed if this is likely to be diagnostically useful. At present no 'guidelines' exist. Methods An EFNS panel of muscle specialists was set to review relevant studies from PubMed dating as far back as 1/1/1990. Only Class IV studies were available and therefore the recommendations arrived at are 'best practice recommendations' based on information harvested from the literature search and expert opinion. Results Muscle cramps should be recognized while drugs, infections, metabolic/ endocrinological and rheumatological causes of myalgia should be identified from the history and examination and pertinent laboratory tests. A muscle biopsy is more likely to be diagnostically useful if myalgia is exertional and if one or more of the following apply: i) there is myoglobinuria, (ii) there is a second wind phenomenon, (iii) there is muscle weakness, (iv) there is muscle hypertrophy /atrophy, (v) there is hyperCKemia (>2–3× normal), and (vi) there is a myopathic EMG. Conclusions Patients presenting with myalgia can be recommended to have a biopsy based on careful history and examination and on simple laboratory screening.